Evolution and transformation processes of China’s educational policy and governance in 1978-2019 - Vasily B. Kashin; Alexandra D. Yankova (RUDN Journal of World History, 2022)
Since the beginning of the period of reforms and openness, the PRC has constantly promoted a phased reform of the education system to modernize educational functions, rise new builders of socialism and support economic transformations in the country. Due to the active regulatory and management work, described in detail in the article with the help of instrumental observation, China gradually achieved several important results. State educational policy shifted from focusing on expanding the scope and improving the quality of education to its connotation-based development. The study of the Chinese experience of modernization of the education system has not only theoretical, but also practical significance, since successful Chinese examples of deep and rapid transformation of the national administrative system and state functions, as well as a clear adjustment of the characteristics of educational policy to current national priorities can be considered for partial application in other countries, including Russia. In order to adapt elements of the Chinese experience to the realities of other countries, such as Russian Federation, it is necessary to fully understand the context, features and stages of the educational policy evolution of the People’s Republic of China, which is done in this article.